The Use of Mindful Experiental Learning to Improve Students’ Listening Skilll - Syamsia, Syamsia; Adhelien Ode, Thelsya (English Education Journal, 2023)
Listening is a complex and active mental process that involves perception, attention, cognition, and memory.The objective of this research are to find out whether the implementation of mindful experiential learning to improves the student’s listening comprehension and to find out the student’s experience toward the implementation of mindful experiential learning in teaching intensive listening. This research was quantitative research namely experimental design, through quasi-experimental. The researchers used worksheet and interview to collect data. The data obtained from the students' worksheets were analyzed to measure the students' listening comprehension level; the researchers used Google Form to carry out interviews. The data showed that the students' listening effectiveness before and after the treatment is significantly different. It was found in post-test students was higher than the pre-test, it proved that the use of Mindful Experiential Learning in teaching extensive listening can improve the students’ listening comprehension. While the results of the test shown that the significance is 0.096 this value is higher than the level of significance for one tailed-test (0.048). The significance of Using Mindful Experiential Learning for the teacher will apply it as an alternative method especially in teaching English and for the students can be more motivated to practice listening or their motivational function to improve their listening comprehension